Conflict Resolution Education Model Based on Pikukuh (MPRKBP): a Strategy to Strenghthen Local Wisdom-Based Learning in Schools - Puryanto, Sidik (Journal of Education Culture and Society, 2025)
Aim. This study explores the integration of Pikukuh, traditional values from the Baduy community, into conflict resolution education. It examines Pikukuh’s relevance to conflict resolution, identifies suitable theoretical and methodological approaches, develops assessment methods, and evaluates its integration into curricula. Additionally, the study analyses how strengthening local wisdom supports the Sustainable Development Goals (SDGs). Methods. A mixed-methods approach combined quantitative and qualitative research. Data collection included a survey of 160 elementary students, a SWOT analysis with six experts, and interviews on Pikukuh in education. Quantitative data were analyzed using descriptive statistics, while qualitative data were transcribed, coded, and thematically examined to develop an educational model. Results. Findings show that while most students (96.9%) recognize conflicts and their impacts (98.8%), only 68.9% understand conflict resolution, highlighting the need for further education. Experts agree (50%) that Pikukuh enhances conflict resolution skills, fosters peace, and promotes cooperative behavior. Innovative teaching methods, such as role-playing, demonstration and simulations, were identified as effective for embedding Pikukuh values. Conclusion. Integrating Pikukuh bridges local wisdom with modern pedagogy, fostering student character development and social harmony. This approach aligns with SDGs by promoting quality education, peace, and cultural preservation. Incorporating Pikukuh into curricula and extracurricular activities strengthens students’ conflict resolution skills and provides a strategic solution for multicultural education in Indonesia. Cognitive value. Pikukuh-based conflict resolution education lies in its ability to integrate traditional wisdom with modern educational practices to enhance students’ understanding of conflict and its resolution.